ANALISIS PENGEMBANGAN CORPORATE VALUE BERDASARKAN KEPUTUSAN INVESTASI DAN PENDANAAN, STRUKTUR KEPEMILIKAN SERTA KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK - Holil Holil; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACT This research was conducted to analyze the effect of investment decisions, funding decisions, ownership structure, and dividend policy on company value of LQ45 companies listed on the Indonesia Stock Exchange (IDX). The LQ45 company was chosen as the object of research because it is 45 stocks of high quality and most actively traded on the Indonesia Stock Exchange (IDX). The high level of stock trading is a factor of changes in shares listed in LQ54 each period, which then motivates companies to form appropriate decisions in managing the company's finances so that they are always listed in LQ45, so that the development of corporate value is more visible and attractive for investors who want invest in LQ45 companies. The sample in the study was taken using a purposive sampling method. The population in this study were LQ45 companies listed on the Indonesia stock exchange (BEI) for the 2015-2017 period, so that there were 45 companies in the study population. As for those selected according to the specified sample criteria from 3 years (2015-2017) the observation period is 30 companies. Data were analyzed using multiple linear regression analysis with Software SPSS 22 For Windows. Based on the results of simultaneous hypothesis testing shows that investment decisions (PER), funding decisions (DER), ownership structure (KMM) and dividend policy (DPR) significantly influence the company value (PBV). The results of the partial hypothesis test show that investment decisions (PER) and ownership structures (KMM) have no effect on company value, while the funding decisions (DER) and dividend policies (DPR) significantly influence the company value (PBV). Keywords: Corporate value, investment decisions, funding decisions, ownership structure, dividend policy.